2001
DOI: 10.1021/ie0009841
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Critical Micelle Concentrations of Nonionic Surfactants in Aqueous and Nonaqueous Solvents with UNIFAC

Abstract: The UNIFAC group-contribution model is used to predict the critical micelle concentration (cmc) of nonionic surfactants in aqueous and nonaqueous solvents. For predicting the cmc, the phase-separation thermodynamic framework approach is used, where the micellar phase is approximated as a second liquid phase resulting from the liquid−liquid equilibrium between the solvent and the surfactant. The necessary activity coefficients are predicted by UNIFAC. The most promising UNIFAC model for this purpose was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…This dual tendency is responsible for adsorption of surfactants at interfaces and for the formation of such aggregates as micelles. The hydrophobic part of the aggregate forms the core of the micelle, while the polar head groups are located at the micelle-water interface in contact with and hydrated by a number of water molecules [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dual tendency is responsible for adsorption of surfactants at interfaces and for the formation of such aggregates as micelles. The hydrophobic part of the aggregate forms the core of the micelle, while the polar head groups are located at the micelle-water interface in contact with and hydrated by a number of water molecules [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the CMC value decreased in the following order. calcium oxalate < calcium fluoride < calcium chloride < calcium acetate Ponganis et al [13] interpreted the turbidity observed in aqueous solutions of SDS containing [Cu(phen) 2 ] + (phen=1,10-phenanthroline) below the CMC occurred from ion pair formation between the metal chelate ion and the polar head groups of the surfactant anions. Meisel et al [14] compared the absorption spectra of [Ru(bpy) 3 ] 2+ (bpy=2,2′-bipyridine) in aqueous SDS solutions with those in aliphatic alcohols and observed evidence that [Ru(bpy) 3 ] 2+ interacted with the hydrocarbon part rather than the polar head group of SDS.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using the UNIFAC model, with different approaches, to predict CMC's has been evaluated by different authors [16,17,24]. One of the approaches assumes that surfactants and solvent are part of a mixture, which split into two liquid phases at some specific Gibbs free energy [16,17].…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 99%
“…One of the approaches assumes that surfactants and solvent are part of a mixture, which split into two liquid phases at some specific Gibbs free energy [16,17]. Another approach consists in assuming a pseudo micellar phase solely composed by surfactants in equilibrium with a solution of surfactant monomers dissolved in the solvent (water in this case).…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 99%
See 1 more Smart Citation